Detection of ALS3 and EAP1 gene expresssion in Candida albicans and Candida maltosa biofilms by FISH - Romero, Danitza Xiomara; Cárdenas, Oscar Víctor; Álvarez, María Teresa (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Biofilm is regarded as universal forms of microorganism life in aquatic and industrial wastewater systems as well as in a large number of environments and medical devices relevant for public health, where the exact mechanisms by which biofilm-associated microorganisms elicit infection diseases are still poorly understood. Candida biofilm formation is regulated by different mechanisms where adhesins play a clue role in the yeast attachment to certain surfaces. These adhesins are encoding by ALS3, HWP1 and EAP1 genes among others and they are also considered as Candida virulence factors. Methodologies use to study biofilm productions are intended to verify the biofilm composition, formation steps, tridimensional structure and might facilitate the monitoring of biofilm regarding, antibiotic resistance, degradations, inhibitors, enhanciement biofilm formation and other features. Here, FISH expression a modified method to detect gene expression in situ was used in order to detect ALS3, HWP1 and EAP1 in C. albicans and C. maltosa biofilms, constituting a useful tool to monitor biofilm formations. In this regard, ALS3 expression was identified in C. albicans and C. maltosa biofilms.